The Power of Language, Learning and Socialization: Romani and Ebonics. Issue 1 (2nd January 2017) - Eckert, Eva
ABSTRACT: This article draws attention to the role one's language plays in socialization and explains the misunderstandings and conflicts over integration of the Roma in the Czech Republic. Recognizing the role of home language leads to successful socialization. By not demanding that schools account for home language in the process of teaching, the Roma have implicitly agreed that Czech is the natural way through which children of diverse cultural backgrounds access education and adapt. Children of minorities and namely, the Roma, have been disadvantaged by cultural assumptions enabling teachers, curricula, and textbooks to construct the profile of a Czech student in a way that precludes his or her multicultural origin. To compare, the study provides insight into the conflict between Standard American English and Afro-American English and highlights its factors, legal resolutions, and contemporary situation. The article also reviews research on bilingual classrooms and learning in the United States and suggests that it is relevant to the contentious interrelationship of standard Czech and Romani at schools.